Kajian semiotik dalam novel-novel Mochtar Lubis - Kim, Jang Gyem (Universiti Kebangsaan Malaysia, 2008)
Mochtar Lubis plays an important role in the Indonesian literary world. He is also one of the most respected Indonesian journalists in Indonesia. This paper involves a semiotic analyses of six of his fiction works. It is evident that in his works, Mochtar Lubis is concerned with issues that commonly affecting people in social and cultural dynamic. Such a phenomenon is important for studying intertextuality among his works. It is clear that in each novel, Mochtar Lubis tends to refer to his previous works. Quotation and references to other works are often utilized for textual signification. To understand Mochtar Lubis works, both internal and external textual devices have to be scrutinized